Patchoulene epoxide mitigates colitis and hepatic damage induced by dextran sulfate sodium by regulating the colonic microbiota and purine metabolism - Chen, Liping; Xie, Lili; Wang, Lifen; Zhan, Xueli; Zhuo, Zhenjian; Jiang, Susu; Miao, Lei; Zhang, Xinxin; Zheng, Weiming; Liu, Tzu-Ming; He, Jing; Liu, Yuhong (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC) is often characterized by dysbiosis of the colonic microbiota and metabolic disturbances, which can lead to liver damage. Patchoulene epoxide (PAO), a tricyclic sesquiterpene derived from the aged essential oil of Pogostemonis Herba, is known for its anti-inflammatory and ulcer-healing properties. However, its dual protective role against UC and liver injury remains largely unexplored. This study aims to elucidate the protective effect and underlying mechanism of PAO against dextran sulfate sodium (DSS)-induced UC and liver injury in mice.MethodsColitis and liver injury in mice were induced by adding 3% DSS to their drinking water continuously for 7 days, and PAO at the doses of 20 and 40 mg/kg was administered orally to mice daily from the first day until the experimental endpoint. Stool consistency scores, blood stool scores, and body weights were recorded weekly. Disease activity index (DAI) was determined before necropsy, where colon and liver tissues were collected for biochemical analyses. Additionally, the fecal microbiome and its metabolites of treated mice were characterized using 16S rRNA amplicon sequencing and metabolomics.ResultsPAO significantly reduced the disease activity index and mitigated colonic atrophy in UC mice. It also improved colonic and hepatic pathological changes by safeguarding tight and adherens junctions, and suppressing the generation of pro-inflammatory cytokines and lipopolysaccharide. These beneficial effects were attributed to PAO’s capability to regulate the colonic microbiota and metabolic processes. PAO was found to enhance the diversity of the colonic microbiota and to shift the microbial balance in UC mice. Specifically, it restored the microbiota from an Akkermansia-dominated state, characteristic of UC, to a healthier Muribaculaceae-dominated composition. Furthermore, PAO corrected the colon metabolic disturbance in UC mice by modulating the purine metabolism, notably increasing the abundance of deoxyadenosine, adenosine and guanine in UC mice.ConclusionsThe therapeutic effect of PAO on UC and liver injury was mainly attributed to its regulation of colonic microbiota and purine metabolism. These insights emphasize the overall therapeutic benefits of PAO in treating UC and liver injury.